Tissue-engineered skeletal muscle constructed by human gingival fibroblasts - P Song; XQ Liu; W Huang; FF Wang; WJ Li; LM Zhang; J Wang (European Cells & Materials)
Objective: Tissue engineering technology has achieved remarkable progress in the regenerative repair treatment of many diseases, but the problems in seed cells and scaffold materials are far from being solved. Here, skeletal muscle-like cells (SMLCs) differentiated from human gingival fibroblasts (HGFs) were implanted into bioresorbable collagen membrane (Bio-Gide) scaffold materials to construct tissue-engineered skeletal muscle (TESM), followed by implantation into injured temporal muscle of Beagle dogs to explore the feasibility of constructing TESM and provide new ideas for research on repair and treatment of muscle injuries. Methods: HGFs were induced to differentiate into SMLCs by using azacytidine (5-aza). HGFs and SMLCs were identified by immunofluorescence and immunocytochemistry assay. Western blot was used to detect the levels of skeletal muscle cells (SMCs)-associated markers in differentiated HGFs. The SMLCs on Bio-Gide and acellular dermal matrix (ADM) scaffold materials were identified by hematoxylin-eosin (HE) staining and immunocytochemical staining. Transmission electron microscopy (TEM) was used to observe the ultrastructure of SMLCs. The surface ultrastructure of Bio-Gide and ADM scaffolds were observed by scanning electron microscopy (SEM). HE staining and Masson staining were conducted to measure the effects of TESM on the recovery and regeneration of injured skeletal muscle tissues. Results: Levels of SMCs-associated markers myosin, myogenic factor 5 (Myf5), and myoblast determination (Myod) in HGFs were the highest at 28 days after treatment with 5-aza. After the induced cells were inoculated on the Bio-Gide scaffold, a large number of cells were attached to the inner surface of the Bio-Gide scaffold, and the cells were in the shape of long columns on the porous and thick collagen, and the cell proliferation was active. The TESM constructed by combining HGFs induced differentiated SMLCs with Bio-Gide scaffolds not only has certain morphological characteristics of skeletal muscle, but also has anti-stress function to a certain extent after culture in vivo. Conclusions: HGFs have the ability to differentiate into SMLCs, and Bio-Gide is a feasible material for TESM. TESM constructed by combining HGFs induced differentiated SMLCs with Bio-Gide scaffolds facilitated the recovery and regeneration of injured skeletal muscle tissues, thus providing a new idea for the treatment of muscle injury.